Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1007/s004420050879
|View full text |Cite
|
Sign up to set email alerts
|

Do submerged aquatic plants influence their periphyton to enhance the growth and reproduction of invertebrate mutualists?

Abstract: It has been suggested that submerged aquatic plants can influence the nutritional quality of the periphyton which grows on their surfaces, making it more nutritious for grazing invertebrates, particularly snails. In return, these grazers might preferentially feed on the periphyton and clear the plants of a potential competitor, with the plants and grazers both gaining from this mutualistic relationship. A highly replicated experiment was conducted, in which the nature of the plant (isoetid and elodeid types co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 52 publications
2
58
0
2
Order By: Relevance
“…Because macrophytes are central to sustained water transparency in shallow-water, nutrient-rich habitats (e.g., Scheffer, 1998), heavy periphyton grazers with diurnal habits may effectively contribute to stabilize a macrophyte-dominated clear-water state even in otherwise phytoplankton-favoring nutrient-rich habitats. Physid commonness, high effectiveness as periphyton grazers (Jones et al, 1999;Lombardo, 2001), and highly active (feeding) behavior (this study), suggest that P. acuta may indeed play a keystone role in macrophytebased littoral food webs, as suggested by Lombardo (2001), and more so than other snail species with similar diurnal habits.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Because macrophytes are central to sustained water transparency in shallow-water, nutrient-rich habitats (e.g., Scheffer, 1998), heavy periphyton grazers with diurnal habits may effectively contribute to stabilize a macrophyte-dominated clear-water state even in otherwise phytoplankton-favoring nutrient-rich habitats. Physid commonness, high effectiveness as periphyton grazers (Jones et al, 1999;Lombardo, 2001), and highly active (feeding) behavior (this study), suggest that P. acuta may indeed play a keystone role in macrophytebased littoral food webs, as suggested by Lombardo (2001), and more so than other snail species with similar diurnal habits.…”
Section: Discussionsupporting
confidence: 68%
“…Physids in particular are capable of exerting top-down control of epi/periphyton even in the presence of strong bottom-up forces (high nutrient concentrations: Jones et al, 1999;Lombardo, 2001). High grazing rates suggest that snails may play a major role in shallow-water habitats, maintaining or promoting high water clarity in eutrophic waters by enhancing macrophyte well-being through continuous removal of competing epiphyton (Brošnmark and Weisner, 1992;Lombardo, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Previous observations already indicated a negative relationship between Elodea and algae or cyanobacteria. Hasler and Jones (1949) reported lower phytoplankton densities in the presence of www.elsevier.com/locate/aquabot Aquatic Botany 85 (2006) 203-211 E. canadensis, and both E. canadensis and E. nuttallii were less covered with epiphytes than other submersed macrophytes (Wium-Andersen, 1987;Jones et al, 1999;Gross et al, 2003b). Our research revealed that Elodea might be chemically defended against insect herbivores (Erhard, unpublished results), and waterweeds may also produce secondary metabolites that inhibit the growth of co-occurring primary producers.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, macrophytes can provide habitats and foods for aquatic animals, which can increase spatial heterogeneity and allow more species of various ecological niches to coexist in a macrophytedominated lake (Padial et al, 2009;Bazzanti et al, 2010;Robinson and Doering, 2013). In addition, macrophytes provide more surface area for attachment by periphytons, which are a major component in the diet of macroinvertebrates (Jones et al, 1999;Cai et al, 2011). Our findings showed that scrapers had the highest abundance in the macrophyte-dominated regions (Fig.…”
Section: Relationship Between Benthic Macroinvertebrate Assemblages Amentioning
confidence: 62%